SKRINING SENYAWA METABOLIT SEKUNDER DAN UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETILASETAT DAUN WEDUSAN (Eupatorium odoratum) - Purwati Purwati; Undri Rastuti (Molekul, 2009)
Oxidation process is a natural process which always occurs in fat. The process affects and decreases the fat quality. Oxidation in fat can be hampered by the addition of antioxidant. Antioxidant activity of wedusan leaf has to be studied to know the possibility of wedusan leaf as an antioxidant. Hence, the aims of the research were to determine the antioxidant activity of ethyl acetate extract of wedusan leaf using TBA method, and to compare the antioxidant activity of wedusan leaf and that of BHT. The research method consisted of sample preparation, extraction, and determination of antioxidant activity using TBA method. Wedusan leaf was extracted by maceration using n-hexane and ethyl acetate solvents. The n-hexane extract was 2.90 gram, whereas ethyl acetate extract was 13.12 gram. Based on qualitative screening on secondary metabolites, ethyl acetate extract contained flavonoid. The results from GC-MS indicated that ethyl acetate extract contained methyl heptadecanoic, methyl-13-octadecenoic, 14,16-octadecadienal, and octadecanoic acid. The order of inhibition activity of antioxidant were 0.05% (w/v) of BHT > 0.15% (w/v) of ethyl acetate extract > 0.10% (w/v) of ethyl acetate extract > 0.05% (w/v) of ethyl acetate extract.